PHYTOCHEMICAL COMPOSITION AND ANTICANCER ACTIVITY OF SEAWEEDS ULVA LACTUCA AND EUCHEUMA COTTONII AGAINST BREAST MCF-7 AND COLON HCT-116 CELLS - Ade Arsianti; Fadilah; Fatmawaty; Wibisono, Lies K; Kusmardi; Azizah, Norma Nur; Putrianingsih, Rista; Murniasih, Tutik; Rasyid, Abdullah; Pangestuti, Ratih (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Objective: this study is aimed to develop marine resources which is focused on the determination of Â phytochemical composition and exploration of seaweeds Ulva Lactuca and Eucheuma cotonii, as a potentialÂ anti-breast cancer and anti-colorectal cancer agents. Â Methods: Seaweeds Ulva Lactuca collected from Parangtritis beach, Yogyakarta, Central Java, Indonesia. Whereas Eucheuma cottonii collected from Salemo island, South Sulawesi, Indonesia. Seaweeds U. lactuca and E. cottonii were macerated in organic solvents, n-hexane, chloroform, ethyl acetate and ethanol, respectively. After maceration for three days, the mixture was filtered, the filtrate was concentrated by rotary evaporator. The concentrated extract of n-hexane, ethyl acetate, ethanol and chloroform were then analyzed by thin layer chromatography. Phytochemical test of the concentrated extract were conducted to identify the metabolites containing in the seaweeds. Furthermore, the cytotoxic activity of the n-hexane, ethyl acetate, ethanol and chloroform extract of Ulva Lactuca and Eucheuma cotonii were evaluated as a growth inhibitor of breast MCF-7 and colorectal HCT-116 cancer cells by MTT cell proliferation assay. Â Results: Phytochemical testÂ for the Â concentrated extracts of Ulva Lactuca showed the positive result for metabolites of Â steroids, glycosides, flavonoid,and tannin. While Â the concentrated extracts of E. cottonii showed positive result for metabolites of steroids, glycosides, and flavonoid. Both concentrated extracts of Ulva lactuca and Eucheuma cotonii exhibited anticancer activity against breast MCF-7 and colorectal HCT-116 cells with IC50 ranging ofÂ 21 Âµg/mLÂ toÂ 99 Âµg/mL . Â Conclusion: Our results clearly demonstrate seaweeds Ulva Lactuca and Eucheuma cotonii as a promising candidates for theÂ new anti-breast and anti-colorectal cancer agents. Â Keywords: Phytochemistry, Ulva Lactuca, Eucheuma cotonii , anticancer, breast MCF-7, colorectal HCT-116